Políticas educacionais para diversidade sexual e de gênero: limites e possibilidades para a promoção da equidade social - Candeloni, Caroline Fabiane (2017)
The present dissertation deals with public policies and school practices related to sexual and gender diversity in Basic Education, in which a qualitative research was done using the research methodology of bricollage with teachers and managers, of two state public network schools of Santa Maria - RS and, also, two other schools of the municipal public network of the same city. This research has as its main objective to understand the limits and possibilities of legislation and educational policies in relation to sexual and gender diversity, with a view to overcoming inequalities, prejudices and discrimination towards those who deviate from the standards of hegemonic gender and sexual orientation, as well as the recognition and appreciation of diversity within the school. This work is anchored in gender research, in Queer studies, and in human rights. In addition, it refers to authors such as Michel Foucalt, Joan Scott, Guacira Lopes Louro, Judith Butler, Marilena Chauí and Tomas Tadeu Silva. First, a brief search for the state of knowledge about gender and sexual diversity in legislation, educational policies and school practices was carried out to check what has already been done about it and to map the legislation and educational policies for sexual and gender diversity. Afterwards, a literature review was carried out with the purpose of conceptualizing sexual and gender diversity, based on the authors that deal with these themes and, in addition, to highlight the role of education in the recognition of sexual and gender diversity. Subsequently, legislation and educational policies for sexual and gender diversity were selected and analyzed, aiming to understand the advances and setbacks of these over the years, more precisely from the second half of the twentieth century to the present day. Finally, an investigation was made in the schools mentioned above, seeking to understand how, in them, the current legislation and educational policies for sexual and gender diversity are made effective.